Analisis Hukum Tentang Hak Dan Kewajiban Wisatawan Dalam Perjanjian Dengan Hotel Terhadap Wanprestasi Dan Penyelesaiannya (Studi Kedas Hotel dan Resort) - Kasih, Niluh Ketut Candra (Innovative: Journal Of Social Science Research, 2025)
In the modern era, recreation and tourism have become essential needs that support people's quality of life. Accommodations such as hotels and resorts play a key role in providing tourist comfort. This study examines the rights and obligations of tourists under agreements with hotels, possible forms of breach of contract, and dispute resolution mechanisms between tourists and Kedas Hotel and Resort. The method used is a normative juridical approach to study legal norms and an empirical approach through interviews with relevant sources. The results indicate that tourists have the right to services according to booking information, security, cleanliness, and additional amenities such as breakfast. Conversely, tourists are obliged to make payments on time and maintain order during their stay. Fulfilling these rights and obligations can prevent breach of contract. If breach of contract does occur, resolution can be achieved through mediation and litigation mechanisms. This study recommends that the legal team at Kedas Hotel and Resort increase education for prospective tourists regarding their rights and obligations throughout the booking process and their stay to minimize disputes.